Existence results for a coupled system of higher-order nonlinear differential equations with integral-multipoint boundary conditions - AHMAD, Bashir; NTOUYAS, Sotiris K.; ALSAEDI, Ahmed; WALI, Ammar B. (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
In this paper, we establish the existence and uniqueness criteria for solutions of an integral-multipoint coupled boundary value problem involving a system of nonlinear higher-order ordinary differential equations. We apply the Leray-Schauder’s alternative to prove an existence result for the given problem, while the uniqueness of its solutions is accomplished with the aid of Banach’s fixed point theorem. Examples are constructed for illustrating the obtained results. Mathematics Subject Classification (2010): 34A34, 34B10, 34B15. Received 13 October 2024; Accepted 10 January 2025.